2021
DOI: 10.3390/w13060776
|View full text |Cite
|
Sign up to set email alerts
|

Improving Radar-Based Rainfall Forecasts by Long Short-Term Memory Network in Urban Basins

Abstract: Radar-based rainfall forecasts are widely used extrapolation algorithms that are popular in systems of precipitation for predicting up to six hours in lead time. Nevertheless, the reliability of rainfall forecasts gradually declines for heavy rain events with lead time due to the lack of predictability. Recently, data-driven approaches were commonly implemented in hydrological problems. In this research, the data-driven models were developed based on the data obtained from a radar forecasting system named McGi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…As suggested in the package documentation and literature [59], [60], the parameter for an RF should be sufficiently large. The parameters and were tuned in the ranges of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and [1000-2000], respectively, with the grid search method.…”
Section: Model Implementationmentioning
confidence: 99%
“…As suggested in the package documentation and literature [59], [60], the parameter for an RF should be sufficiently large. The parameters and were tuned in the ranges of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and [1000-2000], respectively, with the grid search method.…”
Section: Model Implementationmentioning
confidence: 99%
“…The authors showed that their approach outperforms the EMOS (Ensemble Model Output Statistics) method. Using the data obtained from a radar forecasting system named McGill Algorithm for Precipitation nowcasting by Lagrangian Extrapolation (MAPLE) (Germann and Zawadzki, 2002) and ground rain gauges, Nguyen et al (2021) employed LSTMs. They showed that LSTMs significantly improved MAPLE forecasts for South Korea.…”
Section: Forecast Improvementmentioning
confidence: 99%
“…Similarly, for rainfall intensity, both statistical analysis of time series and ML models have been proposed to forecast precipitation over successive days [28], [29], [30]; successive hours [31], [32], [33], [34], [35]; or sequences of shorter intervals [36]. For short-term forecasting (i.e., limited to a few hours ahead), the input variables generally consist of the rainfall intensity, and sometimes other meteorological quantities, recorded over a period going from the last 45 min to the last 3 h [31], [32], [33], [34], [35], [36]. As for wind, the most recent contributions [29], [30], [34], [35] focus on the LSTM network.…”
Section: Introductionmentioning
confidence: 99%
“…For short-term forecasting (i.e., limited to a few hours ahead), the input variables generally consist of the rainfall intensity, and sometimes other meteorological quantities, recorded over a period going from the last 45 min to the last 3 h [31], [32], [33], [34], [35], [36]. As for wind, the most recent contributions [29], [30], [34], [35] focus on the LSTM network. According to the results reported in previous papers, Barrera-Animas et al [35] state that forecast models based on LSTM networks "outperform other models in the task of forecasting rainfall on an hourly, daily, and monthly basis.…”
Section: Introductionmentioning
confidence: 99%